CancerGeneNet: linking driver genes to cancer hallmarks. Issue Volume 48:Issue D1(2020) (10th October 2019) - Iannuccelli, Marta; Micarelli, Elisa; Surdo, Prisca Lo; Palma, Alessandro; Perfetto, Livia; Rozzo, Ilaria; Castagnoli, Luisa; Licata, Luana; Cesareni, Gianni
Abstract: CancerGeneNet (https://signor.uniroma2.it/CancerGeneNet/ ) is a resource that links genes that are frequently mutated in cancers to cancer phenotypes. The resource takes advantage of a curation effort aimed at embedding a large fraction of the gene products that are found altered in cancer cells into a network of causal protein relationships. Graph algorithms, in turn, allow to infer likely paths of causal interactions linking cancer associated genes to cancer phenotypes thus offering a rational framework for the design of strategies to revert disease phenotypes. CancerGeneNet bridges two interaction layers by connecting proteins whose activities are affected by cancer drivers to proteins that impact on the 'hallmarks of cancer'. In addition, CancerGeneNet annotates curated pathways that are relevant to rationalize the pathological consequences of cancer driver mutations in selected common cancers and 'MiniPathways' illustrating regulatory circuits that are frequently altered in different cancers.